2021
DOI: 10.4274/tybd.galenos.2021.37167
|View full text |Cite
|
Sign up to set email alerts
|

Lactate/Albumin Ratio as a Prognostic Factor for Short-time Mortality in Critically Ill Patients with Coronavirus Disease-2019

Abstract: Objective: The prognostic role of the initial lactate/albumin ratio (LAR) in critically ill patients with coronavirus disease-2019 (COVID-19) remains unknown. This study aimed to evaluate the prognostic value of the initial LAR in predicting 30-day mortality in critically ill patients with COVID-19 and compare the initial level of serum lactate and albumin for mortality prediction. Materials and Methods: A single-center and observational clinical study between April 2020 and December 2020 were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…16 Gök et al, in an intensive care study in which they investigated the relationship between lactate/albumin ratio and short-term mortality, showed that lactate/albumin ratio could be used as a prognostic factor in SARS-CoV-2infected patients with an AUC value of 0.824. 17 Although there was a difference between the mortality and survivor groups in terms of lactate/albumin ratio as a result of the univariate test, lactate/albumin ratio had the lowest AUC value of 0.641 in the ROC analysis, indicating that it could not be accepted as a good predictor. 6 The first and main limitation of our study was that it was designed retrospectively.…”
Section: Discussionmentioning
confidence: 86%
“…16 Gök et al, in an intensive care study in which they investigated the relationship between lactate/albumin ratio and short-term mortality, showed that lactate/albumin ratio could be used as a prognostic factor in SARS-CoV-2infected patients with an AUC value of 0.824. 17 Although there was a difference between the mortality and survivor groups in terms of lactate/albumin ratio as a result of the univariate test, lactate/albumin ratio had the lowest AUC value of 0.641 in the ROC analysis, indicating that it could not be accepted as a good predictor. 6 The first and main limitation of our study was that it was designed retrospectively.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, Gök and colleagues (2021) evaluated the L/A ratio in patients with COVID-19, reporting its superior diagnostic accuracy for predicting 30-day mortality compared to lactate and albumin alone [ 17 ]. In our study, we observed that patients with sepsis exhibited higher serum albumin and platelet levels than those with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Non-survivors exhibited higher lactate levels (2.77 vs. 1.73 mmol/L, p < 0.001) and lower albumin levels (2.73 vs. 2.95 g/dL, p < 0.001) compared to survivors. The L/A ratio had an AUC of 0.824 (p < 0.001), surpassing serum albumin levels (AUC = 0.644) and serum lactate levels (AUC = 0.795) [ 17 ]. Patients with an L/A ratio >0.60 upon ICU admission had organ failure and higher APACHE-II scores (p < 0.001), establishing it as an independent 30-day mortality risk factor (HR = 10.615, p < 0.001, 95% CI [5.673, 19.865]).…”
Section: Discussionmentioning
confidence: 99%